Evaluasi Mutu Fisik Formula Body Butter Ekstrak Etanol Kulit Buah Manggis (Garcinia mangostana L.) - NI MADE DHARMA SHANTINI SUENA; NI PUTU UDAYANA ANTARI; ERNA CAHYANINGSIH (JURNAL ILMU KEFARMASIAN INDONESIA, 2017)
The rind of the mangosteen (Garcinia mangostana L.) contains many xanthones which have anti-infl ammatory and antioxidant activity that can counteract free radicals and prevent or inhibit cell degeneration (inhibiting aging). Utilization of mangosteen rind generally in the form of powder capsule. The lack of utilization in topical dosage forms makes the researcher interested in making a body butter of ethanol extract of mangosteen rind and evaluating its physical quality. Simplicia of mangosteen rind were dried using oven at 50 °C. Mangosteen rind extract was obtained from the maceration of simplicia powder with 96% ethanol solvent. The formula of body butter mangosteen rind extract is prepared based on the literature study. The body butter was evaluated for organoleptic, pH, adherence, spreading, homogeneity test, and physical stability test for five months. Besides using literature standards, researchers also using body butter that has been market legally as a comparison in evaluated its physical quality. Based on the statistical analysis, it can be concluded that the preparation of body butter extract of mangosteen rind has a good physical quality compared with the body butter that has been market legally. Physical stability for five months showed that the body butter of mangosteen rind extract was stable.